Analisis Efektivitas Kebijakan Transfer Pricing Dalam Menangkal Penghindaran Pajak Pada KPP Madya Jakarta Pusat Tahun 2018- 2019 - Depi Jaenudin; Chairil Anwar Pohan (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Taxes are one of the largest sources of state revenue in Indonesia apart from the oil and gas and non-oil and gas sectors. As one of the sources of state revenue, taxes are placed in the top position as the main source of revenue in increasing the state treasury. This is reflected in the posture of the 2018 State Budget, that tax revenue was targeted at IDR1,618.1 trillion of the total State Revenue Budget of IDR1,894.7 trillion (www.kemenkeu.go.id/apbn2018). As a solution to the problem, the government establishes a transfer pricing policy in supervising taxpayer. This research was conducted with the aim of analyzing the effectiveness of the transfer pricing policy in counteracting tax avoidance at Central Jakarta Intermediate Tax Office as well as inhibiting and supporting entities in the transfer pricing policy. This study used a qualitative method with a descriptive approach. Data collection was carried out through interviews, observation, and documentation. The research subject was the Central Jakarta Intermediate Tax Office. The results showed that the effectiveness of the transfer pricing policy in preventing tax avoidance on the research subjects was quite good; however, there were still complaints regarding the transfer pricing documents. The inhibiting entities were the lack of policy dissemination, level of knowledge and ability of taxpayers, while the driving entities were good taxpayer compliance, firmness of the DGT, and good communication. The conclusion that can be drawn is the effectiveness of the transfer pricing policy that has been implemented has been quite successful because it meets the indicators of the theory used and the achievement of policy goals and objectives.